Half-top-hat keratoplasty is effective method for bullous keratopathy treatment - S. V. Trufanov (Oftalʹmologiâ, 2014)
Purpose: to evaluate outcomes of the half-top-hat keratoplasty.Methods: the study included 58 eyes that had bullous keratopathy and underwent half-top-hat keratoplasty.Results: 40 (69%) patients had clear corneas whole period of observation. Graft rejection occurred in 1 eye. Mean BSCVA was0.47±0.21. Average astigmatism was 5.0±2.1 D. Mean cell endothelial count in 2 years was 2189±399 cell/mm2.Conclusion: Half-top-hat keratoplasty is effective method for bullous keratopathy surgical treatment. the operation is equal pen- etration keratoplasty in refractive results and operation time. But time of rehabilitation is shorter, sealing is better, cell endothelialcount is greater.